Possible function of the c-myc product: promotion of cellular DNA replication. - Iguchi-Ariga, S M (1987)
We have recently cloned a plasmid, pARS65, containing the sequences derived from mouse liver DNA which can autonomously replicate in mouse and human cells (Ariga et al., 1987). In this report, we show that replication of pARS65 in HL-60 cells can be inhibited by co-transfection with anti-c-myc antibody. In an in-vitro replication system using HL-60 nuclear extract, pARS65 functioned as a template. This in-vitro replication was also blocked by addition of anti-c-myc antibody. Specific binding activity of the c-myc product to pARS65 was detected by an immunobinding assay, suggesting that the c-myc protein promotes DNA replication through binding to the initiation site of replication. This has been substantiated using the antibody to help isolate a human DNA segment that can autonomously replicate in the cells.